Analisis Pengaruh Work-Life Balance Dan Motivasi Kerja Terhadap Kinerja Karyawan Di Pt Bank Syariah Indonesia Kantor Area Saharjo – Jakarta Selatan - Azzahra Nasyatra Sulindra; Kurniawati, Dewi; Indra Ade Irawan (Fakultas Ekonomi dan Bisnis Universitas Pancasila, 2025)
This research aims to determine the influence of Work-Life Balance and Work Motivation on Employee Performance at PT Bank Syariah Indonesia, Saharjo Area Office. Respondents in this study used employees of PT Bank Syariah Indonesia, Saharjo Area Office. The sampling method used was calculated using the Slovin formula with a total of 80 respondents tested. The analysis method uses multiple linear regression analysis, classical assumption testing, hypothesis testing, and data processing using SPSS 25. The results of this research show that Work-Life Balance has a significant effect on Employee Performance, Work Motivation has a significant effect on employee performance. Thus, this research concludes that Work-Life Balance and Work Motivation simultaneously influence employee performance at PT Bank Syariah Indonesia, Saharjo Area Office. This research can be used as a study for PT Bank Syariah Indonesia Saharjo Area in improving employee quality and employee performance.